Factors associated with unprotected sex in people who consume sexually explicit media - Telma Maria Evangelista de Araújo; Priscilla Dantas Almeida; André Felipe de Castro Pereira Chaves; Ellen Cristina da Costa Leite Sousa; Rômulo Veloso Nunes; Álvaro Francisco Lopes de Sousa; Inês Fronteira
ABSTRACT Objective: To analyze the factors associated with sex without the use of condoms in consumers of sexually explicit media (SEM). Methods: Cross-sectional study, with a sample of 172 participants selected and collected through social media. To assess the predictors of unprotected sexual practices, the Poisson regression model was used. Values were expressed as a robust prevalence ratio (PR) with their respective confidence intervals. Results: There was a statistically significant association between, the use of condoms and the type of scenes that the participants prefer (p = 0.03), the preference for films with scenes involving unprotected sex or even those that do not care about protection (p = 0.02), the type of pornography watched influencing sexual relations (p = 0.017), and the number of scenes seen per week (p = 0.05). Conclusions: The lack of condom use was associated with the access to erotic scenes.